AN ANTHROPOLOGICAL STUDY OF THE ABO BLOOD GROUP DISTRIBUTION AMONGST THE YORUBA OF NIGERIA (1994)
Twenty-five (25) sub-groups of the Yoruba language sub-family in Nigeria were identified based on such similarities as: territory, dialect, descent, cultural and economic ties. The ABO blood group samples and records of the identified Yoruba sub-groups were analysed and evaluated. These Yoruba sub-groups included: Akoko, Akure, Awori, Bunu, Egba, Egbado. Ekiti, Eko, Ibarapa, Ibolo, Ife, Igbomina, Ijebu, Ijesa, Ijumu, Ikale, Ilaje, Ilorin, Kabba, Ondo, Owo, Owu, Oyo, Remo and Yagba. Frequency distribution and percentiles of the ABO blood groups in each Yoruba sub-groups were determined through statistical analysis and subjected to X2 distribution analysis to detect deviation significance levels about the expected mean of ABO blood groups for the Yoruba language sub-family. The majority of the individual blood group types within the Yoruba sub-groups were of the type 'O'. Percentiles and frequencies for this blood group type for each Yoruba sub-group exhibited two distinct mean pulses. The mean percentiles for the type 'O' blood group were 51.6% and 55% with mean frequency values of 0.718 and 0.742 respectively, indicating the presence of two dialect groups within the Yoruba language sub-family. The Yoruba sub-groups hereby identified from the ABO blood sample analysis and subseguently classed into two dialect groups coincide with the "i" and "u" linguistic dialect areas into which the Yoruba territory of Nigeria is divided, thus confirming the existence of a definite anthropological divide of the Yoruba language sub-family.